The objectives of this research were to identify types of communication media in delivering messages based on media preferences by the community, to identify conservation education effect to the knowledge, attitude and behavior of the community in forest resources conservation, and to identify influence factor in media effectiveness. The research was conducted in 7 villages within Kelay Subdistric and City of Tanjung Redeb for 18 monthes (November 2007 until April 2009) which managed by three p - Agustina Tandi Bunna; E.K.S Harini Muntasib; Burhanuddin M asy’ud (Forum Pasca Sarjana, 2010)
The objectives of this research were to identify types of communication media in delivering messages based on media preferences by the community, to identify conservation education effect to the knowledge, attitude and behavior of the community in forest resources conservation, and to identify influence factor in media effectiveness.  The research was conducted in 7 villages within Kelay Subdistric and City of Tanjung Redeb for 18 monthes (November 2007 until April 2009) which managed by three phases: first phase, preparation in identification and designing media and outreach program using multi-stakeholder workshop, focus group discussion and survey methodology; second phase, implementation activities by delivering the message used various communication media; third phase, evaluation and monitoring of media effectiveness by conducting identification of influence factor and changing in knowledge, behavior and attitude of the community in forest resources conservation.  The results showed that knowledge of the community about the status of the area increased by 48%, where as community knowledge about the status of Sungai Lesanes protected area increased by 60.73%.  Support to the area establish in local community increased by 22.51%.  Based on Likert scale, community attitude was very strong (90.78% to 94.08%), attitude of the community related to the sustainability of forest use was still high (from 73.39% to 74.70%).  Changing behavior after implementation activities was happened, indicated with the communities initiative in land use planning in Sido Bangen village and initiative in arranging participative planning with villager in Merapun and Muara Lesan village.  Developing communication media based on community reference that implemented in environmental education has effective effect in delivering the conservation message to the community. The effective media for rural community generally has characteristic such as visual media and entertainment (e.q. poster and song).     Key words: conservation education, forest resources, knowledge, attitude, behavior